2016
DOI: 10.1016/j.foodchem.2016.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrafiltration process on physico-chemical, rheological, microstructure and thermal properties of syrups from male and female date palm saps

Abstract: This study investigates the effect of the ultrafiltration process on physicochemical, rheological, microstructure and thermal properties of syrups from male and female date palm sap. All the studied syrups switched from pseudoplastic rheological behaviour (n=0.783) to Newtonian behaviour (n∼1) from 10 to 50 °C respectively and present similar thermal profiles. Results revealed that the ultrafiltration process significantly affects the rheological behaviour of the male and female syrups. These differences on rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The activation energy is the energy required to resist against the frictional forces and thus set the molecules in motion, thereby reflecting the effect of temperature change on the viscosity values (Makhlouf-Gafsi et al, 2016). In this work, the Arrhenius model parameters were estimated using Eq.…”
Section: And Discussionmentioning
confidence: 99%
“…The activation energy is the energy required to resist against the frictional forces and thus set the molecules in motion, thereby reflecting the effect of temperature change on the viscosity values (Makhlouf-Gafsi et al, 2016). In this work, the Arrhenius model parameters were estimated using Eq.…”
Section: And Discussionmentioning
confidence: 99%
“…At pH 4, value remote to the pHi which explains the lower quantity of the pectin 0.700.10 remaining after clarification. It's well known that losses of high molecular weight constituents, such as pectin and starch, occur in the clarification processes [MAKHLOUF-GAFSI et al, 2016] .…”
Section: X(20)mentioning
confidence: 99%
“…Our results are not in line with the results obtained by Farahnakya and collab., and Makhlouf-Gafsi and collab., who reported that the date syrup have 80 % of carbohydrates (39.63 % glucose, 33.68 % of fructose and 1.25 % of sucrose) [FARAHNAKYA et al, 2016b, MAKHLOUF-GAFSI et al, 2016 . This difference can be attributed to the variety of date used and concentration of date syrup.…”
Section: X(20)mentioning
confidence: 99%
“…Membrane technology that is widely used in the food industry is the ultrafiltration membrane. This type of membrane can be used to concentrate solution while also providing separation process such wise to retain natural juice constituents like sugar, vitamins, volatile aroma profiles, and improve microbiological quality of permeate [45]. The concern of using membranes is fouling.…”
Section: Membrane Technologymentioning
confidence: 99%
“…The content of sucrose decreases and also causes loss of the pectin content of permeate. From the energy analysis the use of ultrafiltration membranes significantly decreases the heating and cooling area [45].…”
Section: Membrane Technologymentioning
confidence: 99%